2021
DOI: 10.1097/dad.0000000000002061
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Transcranial Extension of Intracranial Meningiomas

Abstract: :Meningiomas are the most common primary central nervous system tumors. These tumors predominantly arise from the neural crest–derived meningothelial cells of the arachnoid dural layer. Intracranial meningiomas are stratified with the World Health Organization classification of tumors. Cutaneous meningiomas present rarely and have their own criteria classification (Lopez classification) of 3 types. The first type is congenital. The second consists of ectopic soft-tissue meningiomas. The third involves tumors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[5,9,20] In the case of extracranial extension of meningioma or intraosseous meningioma, the tumors tend to be slowgrowing. [2,8,11,13,19] In the present case, a subcutaneous mass had grown very rapidly for only 2 months. In a previous review of cranial vault lymphoma, we found that the subcutaneous scalp mass also grew very rapidly before the patient presented for treatment, for a mean duration of 5.8 months.…”
Section: Discussionmentioning
confidence: 52%
“…[5,9,20] In the case of extracranial extension of meningioma or intraosseous meningioma, the tumors tend to be slowgrowing. [2,8,11,13,19] In the present case, a subcutaneous mass had grown very rapidly for only 2 months. In a previous review of cranial vault lymphoma, we found that the subcutaneous scalp mass also grew very rapidly before the patient presented for treatment, for a mean duration of 5.8 months.…”
Section: Discussionmentioning
confidence: 52%